We Are Water Protectors - Lindstrom, Carole 1964-; Goade, Michaela (New York : Roaring Brook Press, 2020)
"Water is the first medicine. It affects and connects us all... When a black snake threatens to destroy the Earth and poison her people's water, one young water protector takes a stand to defend Earth's most sacred resource. Inspired by the many indigenous-led movements across North America, this bold and lyrical picture book issues an urgent rallying cry to safeguard the Earth's water from harm and corruption."--Jacket flap.
Keywords: Water conservation -- Juvenile fiction; Water conservation -- Fiction; Picture books for children